ANALYSIS OF ELECTROMAGNETIC TRANSIENT PROCESSES DURING COMMUTING OF EXTRA-HIGH VOLTAGE POWER TRANSMISSION LINES AND AUTOTRANSFORMERS - KUCHANSKY, VLADYSLAV; KUZNETSOV, VOLODYMYR; KOSHMAN, VSEVOLOD; SABARNO, LYUDMILA; SEVASTYUK, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
During operation, the insulation of electrical equipment and lines is affected by a number of factors: long-term operating voltage, short-term overvoltages, temperature and temperature fluctuations, exposure to moisture and mechanical stress, etc. Overvoltages that occur in electrical systems are one of the factors that significantly affect the reliability of electrical installations. Despite the short-term impact, overvoltages are characterized by a high multiplicity in relation to the long-term operating voltage, an impact on all electrically connected elements of the system regardless of the place of occurrence, a significant increase in the processes of occurrence and development of defects not associated with overvoltages, and accelerated aging of structural units. The most important element of any electrical equipment and any line is insulation, which largely determines the safety of operation, approaches to organizing protection against overvoltages. In the voltage class of 110 kV and above, electrical apparatus and switchgear of gas-insulated design are steadily taking their positions, when the coordination of insulation with operational effects, protection against overvoltage should take into account, in addition to the main insulating structures relative to the ground, also the features of the insulation of switching devices, the influence of adjacent phases. New solutions in the insulation of transformers, generators, motors, synchronous compensators, shunt, arc-suppressing, filtering, current-limiting reactors require taking into account the overvoltage affecting the insulation between turns, layers and coils of one phase. Rethinking and more accurate understanding of the processes, improving technical means allow for more efficient organization of protection against overvoltage. The listed problems are not sufficiently covered in previously published monographs and manuscripts. This brochure is devoted to the analysis of both traditional and new problems of analysis and justification of technologies for protection against overvoltage.